Pengaruh Intensitas Cahaya Yang Berbeda Terhadap Pertumbuhan Berat Mutlak Ikan Lele Dumbo (Clarias Gariepinus) - Yuliandro Erwin Gautama; Sri Oetami Madyowati; Achmad Kusyairi (Universitas Mataram, 2026)
This study aimed to determine the effect of different light intensities on the absolute growth of African catfish (Clarias gariepinus). The experiment was conducted at the Purwosari Fish Hatchery, Magetan, East Java, for 30 days from May 11 to June 9, 2025, using a Completely Randomized Design (CRD) with three treatments (dark 0 lux, shaded 324–830 lux, and bright 6,630–17,070 lux) and nine replications. Data were analyzed using one-way ANOVA followed by the Least Significant Difference (LSD) test at a 5% significance level. The results showed that light intensity significantly affected the absolute growth of African catfish. The bright treatment produced the highest growth (198.98 ± 16.94 g) compared to shaded (155.00 ± 20.45 g) and dark treatments (136.67 ± 23.33 g). Water quality remained within the optimal range for catfish culture, although ammonia levels were higher under bright conditions. These findings indicate that although African catfish are nocturnal, light is still required in intensive aquaculture systems to optimize feeding activity and feed utilization efficiency.